(untitled) (Baghdad Science Journal, 2021)
Mesoporous silica (MPS) nanoparticle was prepared as carriers for drug delivery systems by sol–gel method from sodium silicate as inexpensive precursor of silica and Cocamidopropyl betaine (CABP) as template. The silica particles were characterized by SEM, TEM, AFM, XRD, and N2adsorption–desorption isotherms. The results show that the MPS particle in the nanorange (40-80 nm ) with average diameter equal to 62.15 nm has rods particle morphology, specific surface area is 1096.122 m2/g, pore volume 0.900 cm3/g, with average pore diameter 2.902 nm, which can serve as efficient carriers for drugs. The adsorption kinetic of Ciprofloxacin (CIP) drug was studied and the data were analyzed and found to match well with pseudo-first order kinetic model. The CIP drug-loaded mesoporous silica (CIP-mSiO2) nanoparticles has capacity of about 16.3 mg drug/ mg mSiO2 were achieved, and capable of releasing 26% and 98.6% of their drug content after 90 min in water and PBS solution(pH,7.4) respectively. In-vitro controlled release studies of CIP in Simulated Body Fluid were carried out under stirring conditions. A study on release kinetics and mechanism using Koresmeyer-Pepps model, first order kinetic, and kopcha model shows that the Korsmeyer-Peppas and Kopcha models, both conform more closely to the release data.